Brain lateralization involved in visual recognition of conspecifics in coral reef fish at recruitment. (July 2016) - Roux, Natacha; Duran, Emilio; Lanyon, Rynae G.; Frédérich, Bruno; Berthe, Cécile; Besson, Marc; Dixson, Danielle L.; Lecchini, David
Abstract : In vertebrates, brain functional asymmetries are widespread and increase brain performance. Some species of fishes are known to have brain asymmetries; however, little information is available on brain lateralization in coral reef fishes and the impact this could have during the recruitment phase. In this study, soldierfish, Myripristis pralinia, at the larval and juvenile stage recognized conspecifics through visual cues. Larvae with the ablation of either the right or left telencephalic hemisphere lost the attraction towards conspecific cues. In contrast, juveniles with the ablation of the right (but not left) telencephalic hemisphere still displayed a preference towards conspecific visual cues. These results suggest the left telencephalic hemisphere is responsible for the lateralization process used in the visual recognition of coral reef fish juveniles. The determinism of lateralized perception of conspecifics during fish ontogeny may be a consequence of genetic factors, linked with the metamorphosis processes and/or environmental factors such as predation at recruitment. Highlights: Visual recognition in coral reef fishes is a lateralized process. Left telencephalic hemisphere could be involved in conspecific visual recognition. Lateralization process is established during ontogenetic development. Lateralization process coincides with the recruitment phase.